Nickel-molybdenum hydrogenation catalyst as well as preparation method and application thereof
By doping zirconium in the nickel-molybdenum-alumina catalyst and adjusting the pore structure of alumina using a mixed solution system formed by ammonium zirconium carbonate and aromatic diacid, the problems of poor adsorption performance and slow desorption are solved, the catalytic efficiency and service life are improved, and a more efficient hydrogenation catalytic process is achieved.
Patent Information
- Application Number
- CN202510112680.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-29
AI Technical Summary
The existing nickel-molybdenum-alumina catalysts have poor adsorption performance in long-term reactions and are slow to desorption after adsorption, resulting in a reduced catalytic efficiency.
By doping zirconium on the alumina and using a mixed solution system formed by ammonium zirconium carbonate and aromatic diacid, the pore structure of the alumina is adjusted to form zirconium-doped alumina, and the activity of the catalyst is improved through the synergistic action of nickel and molybdenum.
The catalytic efficiency and service life of the catalyst are improved, the catalytic effect of the catalyst on the system is enhanced, and a more efficient hydrogenation catalytic process is achieved.
Smart Images

Figure CN119897120A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of hydrogenation catalysis, and in particular to a nickel-molybdenum hydrogenation catalyst and a preparation method and application thereof. Background Art
[0002] Nickel-molybdenum hydrogenation catalyst is a catalyst system widely used in industry. It is mainly composed of nickel and molybdenum and is often used in the hydrogenation conversion of chemical raw materials such as natural gas, refineries, water gas and light oil to achieve the purpose of desulfurization.
[0003] Usually, in the presence of hydrogen, COS and CS in raw materials such as coal gas 2 ,RSH,C 4 H 4 S and other organic sulfur 2 The following reaction occurs to convert it into hydrogen sulfide. The specific reaction steps are as follows: COS+H 2 =CO+H 2 S CS 2 +4H 2 =CH 4 +2H 2 S RSH+H 2 =RH+H 2 S C 4 H 4 S+4H 2 =C 4 H 10 +H 2 S Under the action of hydrogen sulfide, the oxidized nickel and molybdenum are further converted into nickel sulfide and molybdenum sulfide, thereby generating catalytic activity, and further catalytic effect on sulfur-containing compounds in the system. The sulfurized catalyst can further carry out hydrogenation catalytic reaction on unsaturated olefins, converting the organic sulfur that is difficult to remove in petroleum products into inorganic sulfur that is easy to remove, so the catalyst has a wide range of applications in the field of petrochemicals.
[0004] Among the products currently on the market, the reaction system with nickel-molybdenum as the main body and alumina as the carrier has been relatively maturely applied. As a commercial-grade catalyst, its sales volume has been rising year by year as fossil raw materials become increasingly important. Although the nickel-molybdenum-alumina system has been maturely applied, its mechanism is still unclear. Alumina has poor adsorption performance in long-term reactions, and slow desorption after adsorption can easily lead to a decrease in the catalytic efficiency of the catalyst. Summary of the invention
[0005] In order to improve the catalytic effect of the above-mentioned catalyst on the system and achieve a more efficient catalytic process, the present application provides a nickel-molybdenum hydrogenation catalyst and a preparation method and application thereof.
[0006] First, the present application provides a method for preparing a nickel-molybdenum hydrogenation catalyst, comprising the following steps: S1, mixing alumina, ammonium zirconium carbonate and aromatic diacid in a solution, heating and sintering to obtain zirconium-doped alumina; S2, impregnating zirconium-doped alumina with a solution containing a nickel salt and a non-metallic salt of heptamolybdate, and then sintering to convert molybdenum and nickel into the form of molybdenum oxide and nickel oxide to obtain catalyst pellets; In step S1, the mass ratio of ammonium zirconium carbonate to aluminum oxide is 0.1-0.2:1. In step S2, the mass ratio of nickel to aluminum oxide is 0.02-0.04:1, and the mass ratio of molybdenum to aluminum oxide is 0.05-0.1:1.
[0007] In the above scheme, a mixed solution system formed by ammonium zirconium carbonate and aromatic diacid is used, and then in step S1, the pore structure of alumina itself is adjusted. In the above process, on the one hand, the mixed coordination structure formed by aromatic diacid and ammonium zirconium carbonate in the solution system is used to make aromatic diacid bind to zirconium ions in the form of ligands, and then after sintering in step S1, a zirconium-doped alumina with a more stable structure is formed, wherein the distance between zirconium ions can be adjusted by aromatic diacids, thereby providing a better catalytic effect, and zirconium has good anti-sintering ability and weather resistance, and its doping can greatly extend the service life of the above catalyst. In addition, after a certain amount of zirconium is doped, it can form a certain amount of zirconium-nickel / zirconium-molybdenum composite system, which may use zirconium to form an intermediate state with a lower energy level, for example, in the reaction process, nickel provides the main hydrogenation catalytic effect, and molybdenum provides the main desulfurization catalytic effect, after completing the above reaction, the reactant bound to molybdenum sulfide can be further obtained by olefin coordination to obtain an intermediate system of zirconium-double bond-molybdenum, thereby utilizing the intermediate process produced to improve the product desorption performance, thereby achieving a faster reaction process.
[0008] In the above steps, the catalyst can be subjected to a forming process such as ball rolling or tablet pressing after step S1 or after step S2, the purpose of which is to make the powdered catalyst pellets / rough products into spherical or tablet-shaped sales products. The order of the forming process has no significant effect on the performance of the catalyst.
[0009] Preferably, in step S1, the molar amount of the aromatic diacid is 2 to 3 times the molar amount of ammonium zirconium carbonate. In order to form a better coordination form, a molar amount higher than that of ammonium zirconium carbonate is used. Each aromatic diacid can form a bidentate ligand. Therefore, zirconium is in a tetracoordinated state, and the excess coordination sites will be chain-linked to coordination ligands such as amino groups and hydroxyls (whose source may be ammonium zirconium carbonate itself or other added additives, such as surfactants, etc.), and at the same time better combined in the alumina system, thereby improving the adhesion performance of the zirconium system on alumina.
[0010] Preferably, the aromatic diacid is 2,2'-biphenyldicarboxylic acid, which has better coordination properties. Compared with phthalic acid, its biphenyl structure provides a certain flexibility, thereby providing a better spacing of the zirconium system and the spacing between zirconium and aluminum, resulting in better catalytic performance.
[0011] Preferably, in step S1, after the mixing and heating is completed, the mixture is first dried at a temperature not higher than 80°C, and then sintered at 600-1000°C for 2-4 hours.
[0012] In the above scheme, the method of drying first and then sintering is adopted. On the one hand, the influence of the solution in the sintering process is reduced to prevent the strength reduction caused by cracking of the overall alumina system. On the other hand, it is more conducive to the integrity of the ash formed by the organic components in the system after sintering, so that zirconium can be better attached to the alumina system, thereby improving the life of the catalyst. Further preferably, in this step, alumina, ammonium zirconium carbonate and aromatic diacid are in the solution, the mass volume ratio of alumina and solution is 60-200g / L, the drying temperature is 60-80°C, and the time is 7-10h. Further preferably, in step S1, the solution is an aqueous solution or a mixed solution of water and alcohol, and the solution contains cellulose ether in a mass concentration of 5 to 15 g / L.
[0013] Adding a certain amount of cellulose ether helps the ammonium zirconium carbonate to form a ligand with the aromatic diacid, so that the coordination system has better dispersion uniformity and stability in the solvent, thereby improving the impregnation and reaction performance of the ammonium zirconium carbonate in the system and optimizing the doping of zirconium. At the same time, cellulose ether itself is not easily adsorbed in alumina, which can reduce the carbonization of alumina during the sintering process, while also maintaining good connection performance between zirconium and aluminum, and improving the life and catalytic effect of the catalyst.
[0014] Preferably, in step S1, the BET specific surface area of the alumina is 140 to 175 m 2 / g.
[0015] Within the above range, alumina can provide sufficient reaction sites and also has reasonable desorption performance, so that it has better desorption properties under the condition of good catalytic performance, thereby improving the efficiency of the catalytic reaction.
[0016] Preferably, in step S2, the sintering temperature is 380-550°C, and the sintering time is 10-30 minutes.
[0017] Through the above sintering process, a better and more uniform mechanical system can be formed, so that the obtained product has stronger apparent performance and mechanical strength.
[0018] Preferably, in the catalyst, the amount of molybdenum added is 2 to 5 times the amount of nickel added.
[0019] In the above scheme, nickel and molybdenum can produce better synergistic effects, making the system have higher catalytic performance and thus providing higher catalytic efficiency.
[0020] In addition, the present application also relates to a catalyst prepared by a method for preparing a nickel-molybdenum hydrogenation catalyst and the use of the catalyst in desulfurization. The catalyst is used after sulfurization, and the operating environment temperature is 200-500°C. After use, it is regenerated by calcination at 300-400°C.
[0021] In summary, the present application provides a method for preparing a nickel-molybdenum hydrogenation catalyst and its application, which utilizes a zirconium-doped system and simultaneously sets a coordination system formed by zirconium and aromatic diacids to control the spacing of zirconium and the spacing between zirconium and aluminum, thereby producing a better catalytic effect and improving the catalytic efficiency and the service life of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of the product prepared in Experimental Groups 1-5 in Example 1 of the present application. DETAILED DESCRIPTION
[0023] The technical solution in this application is further explained through the following specific implementation methods.
[0024] For the following examples, the effect of the catalyst was evaluated through catalytic experiments.
[0025] The catalyst is first sulfided and then the target sample to be treated is evaluated. The sulfidation step is to convert the above catalyst into sulfide by reacting with hydrogen sulfide and hydrogen. The purpose of this step is to convert the metal oxide in the catalyst into metal sulfide to activate the catalyst. The sulfidation temperature can be 300-400°C and the sulfidation time can be 4-8h.
[0026] After sulfurization, DBT (dibenzothiophene) was used as the target sample to be treated for evaluation. The specific experiment was carried out in a high-pressure reactor with n-heptane as the solvent and the temperature set to 350±10°C. In each use, the mass of the catalyst was 0.5g, the concentration of DBT was 2wt%, and the total amount of the reaction system was 100g.
[0027] The reaction time of the above reaction step is 5 hours. During the test, ten reactions are first carried out, and cleaning and drying are carried out after each reaction. Then, calcination is carried out at 300-400°C for 20 minutes, and then five reactions are carried out. Sulfidation treatment is carried out before each reaction. The conversion rates of the first, fifth, tenth, eleventh and fifteenth reactions are recorded.
[0028] Example 1: In this example, different zirconium doping amounts and aromatic diacid addition amounts are compared in different examples through orthogonal comparison to study the effect of the amount of zirconium and aromatic diacid used relative to alumina on the catalytic performance of the system. In this example, 2,2'-biphenyldicarboxylic acid is fixedly used as the aromatic diacid.
[0029] Specifically, the preparation method of the nickel-molybdenum hydrogenation catalyst in the present application is as follows: S1. Ammonium zirconium carbonate and 2,2'-biphenyldicarboxylic acid are dissolved in a water-methanol mixed solution, and alumina is impregnated to load zirconium-organic ligand coordination compound on alumina, and then sintered to load zirconium on alumina. The alumina selected is γ-alumina, and its porosity is 166m as measured by BET method. 2 / g.
[0030] In this step, the solvent is a mixed solution of water: methanol = 4: 1 in mass ratio, which contains 10g / L of carboxymethyl cellulose ether and 50g / L of alumina in mass volume ratio, and different amounts of ammonium zirconium carbonate and 2,2'-biphenyldicarboxylic acid are added. The impregnation temperature is 60°C, and the stirring speed is 120rpm. After 20 minutes, it is first dried at no more than 80°C by vacuum distillation. After drying, the temperature is controlled at 800°C for sintering, and the sintering time is 3h.
[0031] S2. The solid after the sintering is completed is then impregnated with an aqueous solution of nickel nitrate and ammonium heptamolybdate to further load nickel and molybdenum in the above system. Specifically, this step can be prepared by the common method for preparing a catalytic hydrogenation catalyst for a nickel-molybdenum-alumina system on the market. For example, the solution usually uses a solvent with a strong polarity such as water, alcohol, acetonitrile, DMF, etc. By adjusting the mass ratio and concentration of nickel nitrate and ammonium heptamolybdate, the mass of nickel oxide and molybdenum oxide finally loaded on alumina can be controlled (in this embodiment, a mixed solution of water and methanol with a mass ratio of 4:1 is selected), the impregnation time is controlled to 3h, and then the solvent is removed by vacuum distillation or natural drying, and sintered at 600°C for 20min. In this step, for every 50g of alumina, the mass of nickel nitrate used is 4.2g, the mass of nickel element equivalent is 1.5g, the mass of ammonium heptamolybdate used (excluding crystal water) is 8.7g, and the mass of molybdenum element equivalent is 5g. After sintering, spherical particles are prepared by the rolling ball method. It should be noted that there are many options for the molding of the product. For example, a product in the form of a tablet with a specific shape can be obtained by pressing in a mold. It should be noted that the molding step can also be performed after the end of step S1. Considering the microporosity of alumina itself, even if it is immersed in a nickel-molybdenum salt solution after preparation, it can still produce a good load on nickel and molybdenum, and will not affect the catalytic performance of the system.
[0032] pass Figure 1 It can be seen that the solution in this application has a relatively good dense structure, which is relatively uniform as a whole and has good strength. The debris in the figure is generated when the sample is cut, and it does not reflect the strength of the catalyst. In the following experimental results, the debris referred to in the catalyst form is generated during natural use and transportation after production is completed, which reflects the lack of catalyst strength, so the less the better.
[0033] The experimental results obtained by selecting different masses of ammonium zirconium carbonate and 2,2'-biphenyldicarboxylic acid are shown in Table 1.
[0034] 10g / L ammonium zirconium carbonate (excluding crystal water), 9.3g / L 2,2'-biphenyldicarboxylic acid (twice the molar equivalent of ammonium zirconium carbonate)
[0035] Through the above experiments, it can be seen that in the experimental groups 1-5, with the continuous increase of zirconium content, it can be seen in the progress of 1-1 to 1-5 that the catalytic efficiency of C10, C11 and C15 is significantly improved without obvious changes in C1. It can be seen that the addition of zirconium has a significant improvement in the ability to resist sintering. After long-term use, it can be re-enhanced by sintering. The activity of the catalyst itself is basically not lost within 10 cycles. However, the conversion rate does not increase significantly when the added mass of ammonium zirconium carbonate is continuously increased. Instead, the conversion rate of C1 decreases to a certain extent, and its morphology becomes more irregular. The reason may be that the excessive zirconium content has a certain adverse effect on the loading capacity and adsorption capacity of alumina, and also weakens the overall performance to a certain extent.
[0036] By adjusting the mass of the ligand, it can be seen that in the scheme without adding ligands, the catalytic effect of each stage will be significantly reduced. The reason may be that zirconium is easy to agglomerate in the system and its dispersion is poor, which leads to a decrease in the overall catalytic performance of the catalyst. Adding too much ligand will lead to too high residual carbon content after sintering of the system. Although sintering under oxygen-containing conditions will cause part of the carbon to produce carbon dioxide, some of it will still remain, which will lead to a decrease in catalytic performance and the overall tabletability of the catalyst.
[0037] Example 2, based on experimental groups 1-5, different ligands were used in step S1, and the types of ligands and the added concentrations of ligands were selected to conduct orthogonal experiments, and different experimental results were obtained as shown in Table 2.
[0038]
[0039] It can be seen from the data in Table 2 that when aromatic diacids are selected, the ratio between zirconium can be better controlled overall, among which the carboxyl group has a stronger coordination ability with zirconium, and has better catalytic performance than the amino coordination of bipyridine. Compared with phthalic acid and 2-pyridinecarboxylic acid, the experimental results in Example 1 show obvious advantages, proving that in the above coordination system, using 2,2'-biphenyldicarboxylic acid as a ligand has a better effect on improving the catalytic effect.
[0040] Example 3. In this example, the effects of the specific surface areas of different aluminas and the ratios of ammonium zirconium carbonate on the catalytic performance are studied. On the basis of Examples 1-5, the alumina used is replaced, and different aluminas are combined with different amounts of ammonium zirconium carbonate added. The experimental results are shown in Table 3.
[0041]
[0042] It can be seen from the experimental results in the above table that in the case of low specific surface area, the overall catalytic effect will decrease to a certain extent, so increasing the specific surface area is conducive to improving the catalytic effect, but when the specific surface area is too high, such as Examples 3-11 and 3-12, they have a close catalytic effect in the initial cycle, but with the increase in the number of catalytic cycles, the internal carbon deposition phenomenon will become more obvious, and it is difficult to achieve catalyst regeneration after sintering. The overall effect is weaker than that of Experimental Groups 1-5 and Experimental Groups 3-7, 3-8, 3-9 and 3-10.
[0043] Example 4: In this example, the effects of different amounts of nickel and molybdenum added on the catalytic effect of the system are shown in Table 4-1 and Table 4-2. Table 4-1 shows the conversion rate of the C1 cycle, and Table 4-2 shows the conversion rate of the C15 cycle.
[0044]
[0045] The experimental group in Table 4 proved through orthogonal experiments that under different addition amounts of ammonium zirconium carbonate, the addition amounts of molybdenum and nickel to alumina all have similar change trends, and within the range of the mass ratio of nickel to alumina of 0.02 to 0.04:1 and the mass ratio of molybdenum to alumina of 0.05 to 0.1:1, the overall catalytic performance in both C1 and C15 is better, which is a better embodiment. At the same time, in terms of the ratio of nickel to molybdenum, it can be seen that when the addition amount of molybdenum is 2 to 5 times that of nickel, it can achieve better catalytic performance in both C1 and C15 cycles.
[0046] Example 5. In this example, the effects of different sintering temperatures and sintering times in step S1 on the catalytic system are studied. The experimental results are shown in Table 5.
[0047]
[0048] In the above experiment, it can be seen that the sintering time process will have an adverse effect on the overall catalytic effect of the system, especially the catalytic effect after sintering and regeneration in the C11 cycle. It may be that if the zirconium system uses too high a sintering temperature or too long a sintering time during the initial sintering, it will cause its binding performance with the alumina system to weaken, and desorption and other phenomena may occur during the reaction. At the same time, too high a temperature will also cause the strength of the system to decrease, making it difficult for the catalyst as a whole to be pressed and formed in the subsequent preparation process. Sintering time that is too short or sintering temperature that is too low will have a significant adverse effect on the catalytic effect, especially in Comparative Example 1 where subsequent nickel and molybdenum loading steps are directly carried out without sintering. It can be clearly seen that the catalytic effect is reduced. The reason may be that in the unsintered state, the binding performance between zirconium and aluminum is poor, and it is easy to desorb during use, which leads to its inability to fully achieve the catalytic effect.
[0049] Example 6. Based on experimental groups 1-5, this example studies the effect of the amount of carboxymethyl cellulose ether added in step S1 on the catalytic performance. The results are shown in Table 6.
[0050]
[0051] It can be seen from the above experiments that during the addition of carboxymethyl cellulose, the overall catalytic effect of the system tends to increase first and then decrease. The reason may be that the volume expansion effect of carboxymethyl cellulose ether on the system allows zirconium to be more evenly loaded on alumina, but excessive addition of carboxymethyl cellulose ether will result in more ash residue in the system after sintering. In terms of the overall trend, when the amount of carboxymethyl cellulose ether added is too little or not added, the catalytic efficiency after long-term use is reduced, while excessive addition of carboxymethyl cellulose ether will lead to a reduction in its overall catalytic efficiency.
[0052] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a nickel-molybdenum hydrogenation catalyst, characterized in that: The following steps are included: S1, mixing alumina, ammonium zirconium carbonate and aromatic diacid in a solution, heating and sintering to obtain zirconium-doped alumina; S2, impregnating zirconium-doped alumina with a solution containing a nickel salt and a non-metallic salt of heptamolybdate, and then sintering to convert molybdenum and nickel into the form of molybdenum oxide and nickel oxide to obtain a catalyst; In step S1, the mass ratio of ammonium zirconium carbonate to aluminum oxide is 0.1-0.2:
1. In step S2, the mass ratio of nickel to aluminum oxide is 0.02-0.04:1, and the mass ratio of molybdenum to aluminum oxide is 0.05-0.1:
1.
2. The method for preparing a molybdenum-nickel hydrogenation catalyst according to claim 1, characterized in that: In step S1, the molar amount of the aromatic diacid is 2 to 3 times the molar amount of ammonium zirconium carbonate.
3. The method for preparing a nickel-molybdenum hydrogenation catalyst according to claim 1, characterized in that: The aromatic diacid is 2,2'-biphenyldicarboxylic acid.
4. The method for preparing a nickel-molybdenum hydrogenation catalyst according to claim 1, characterized in that: In step S1, after the mixing and heating is completed, the mixture is first dried at a temperature not higher than 80°C, and then sintered at 600-1000°C for 2-4 hours.
5. The method for preparing a nickel-molybdenum hydrogenation catalyst according to claim 4, characterized in that: In step S1, the solution is an aqueous solution or a mixed solution of water and alcohol, and the solution contains cellulose ether at a mass concentration of 5 to 15 g / L.
6. The method for preparing a nickel-molybdenum hydrogenation catalyst according to claim 1, characterized in that: In step S1, the BET specific surface area of the alumina is 140 to 175 m 2 / g.
7. The method for preparing a nickel-molybdenum hydrogenation catalyst according to claim 1, characterized in that: In step S2, the sintering temperature is 380-550°C, and the sintering time is 10-30 minutes.
8. The method for preparing a nickel-molybdenum hydrogenation catalyst according to claim 1, characterized in that: In the catalyst, the added amount of molybdenum is 2 to 5 times the added amount of nickel.
9. A catalyst prepared by the method for preparing a nickel-molybdenum hydrogenation catalyst according to any one of claims 1 to 8.
10. The use of the catalyst prepared by the method for preparing the nickel-molybdenum hydrogenation catalyst according to any one of claims 1 to 8 in a desulfurization process, characterized in that: The catalyst is used after being sulfided in an environment temperature of 200-500°C. After use, it is regenerated by calcination at 300-400°C.